PRE-SERVICE TEACHERS’ CORRECTIVE FEEDBACK IN ORAL INTERACTION: A COMPARISON OF MICROTEACHING AND TEACHING PRACTICUM - Nurrina Nurrina; Jauhar Helmie; Halimah Halimah (Universitas Muhammadiyah Semarang, 2018)
The purpose of this research was to find out the type of corrective feedback used by the pre- service teacher and the differences of teacher’s corrective feedback in microteaching and in teaching practicum. The method of this research was descriptive analysis. The researcher describes the data that has been a transcript, analyzes them and compare the data. The data were taken from observation in microteaching and in teaching practicum, and from the interview. From the research, it can be concluded that the pre-service teacher used four types of corrective feedback in microteaching; they were explicit, recast, clarification request and repetition. While in teaching practicum the pre-service teacher used five types of corrective feedback, they were explicit, recast, metalinguistic request, elicitation, and repetition. It canbe seen that types of corrective feedback used by the pre-service teacher were different both in microteaching the pre-service teacher mostly used recast while in teaching practicum the pre-service teacher mostly used elicitation. There were three reasons why the correctivefeedback different both in microteaching and in teaching practicum; 1) The students in microteaching were the pre-service teacher’s classmate while in the teaching practicum were the real student. 2) In microteaching time as the preparation to teach in the real classroomwhile in teaching practicum as the time to teach real. 3) In microteaching the pre-service teacher in a short time while in teaching practicum the pre-service teacher in a long time. Keywords: oral corrective feedback, pre-service teacher, microteaching and teaching practicum